Advances in the iron-catalyzed direct functionalizations of heterocycles - Pradhan, Chandini; Punji, Benudhar (Synlett, 2023)
Direct functionalization of heterocycles is an advanced strategy for diversifying privileged and biorelevant heterocycle-containing molecules. Particularly, use of the most abundant transition metal, iron, as a catalyst makes this process highly cost-effective and sustainable. Recently, some progress has been realized towards the direct functionalization of heterocycles under iron catalysis. Herein, we present the developments in the C-H bond functionalizations and related reactions of various heterocycles by abundant iron salts. This Synpacts is categorized into different sections based on heterocycles being functionalized, and each section is discussed based on the type of reaction catalyzed by iron. 1 Introduction 2 Functionalization of Indoles 2.1 Alkylation 2.2 Alkenylation 2.3 Other Reactions 3 Oxindoles and isatins 3.1 C-C Bond Formation 3.2 C-Heteroatom Bond Formation 4 Pyridines and Furans 5 Functionalization of Azoles 6 Summary and Outlook
Keywords: Alkylation; azoles; C-H functionalization; heterocycles; indoles; iron; Mechanism